IMPACT OF CORPORATE SOCIAL RESPONSIBILITY TO PROFITABILITY AND FIRM VALUE OF PUBLICLY LISTED CORPORATIONS ENGAGED IN ELECTRICITY, ENERGY, POWER AND WATER - Jimelyn H. Evangelista (LP2M Universitas Bina Mandiri Gorontalo, 2022)
The study is conducted to identify the impact of Corporate Social Responsibility (CSR) using CSR Index disclosure provided by the Global Reporting Initiative (GRI).The researchers used the structural equation model to identify the impact of CSR to firm profitability and firm value. CSR was measured using CSR disclosures index, firm profitability was measured through the use of Return on Assets, Return on Equity and Debt to Equity Ratio, while firm value was measured by Tobin’s Q. Results disclosed that CSR managed to positively impact the firm value. Conversely, CSR failed to explain the changes in profitability. With regards to the moderating variables, firm age was found to positively affect both the profitability and firm value. Firm size, on the other hand, only showed significant impact when moderating CSR and firm value, hence it is insignificant when used as moderator for CSR and profitability. Overall, the results showed that CSR is a good independent variable to measure firm value. These findings provide valuable information not only to the management of companies interested to improve their CSR, profitability and firm value, but also to regulators, shareholders and other stakeholders. Finally, the result of the study may provide additional insights to future researchers in undertaking further study on the impact of corporate social responsibility.